HCG Trigger of GnRH Agonist-Induced Functional Ovarian Cysts Does Not Decrease Clinical Pregnancy Rate in GnRHa Pretreated Frozen Cycles: Evidence From a Retrospective Cohort Study - Zeng, Hong; Zhang, Chen; Zhang, Lei; Liu, Nenghui (Frontiers in Endocrinology, 2022)
Background: GnRH agonist (GnRHa) pretreatment for pituitary downregulation before the frozen-thawed embryo transfer (FET) cycles was increasingly utilized. However, the incidence of functional ovarian cysts following GnRHa pretreatment was inevitable and the treatment of the GnRHa-induced functional cysts was inconsistent. HCG trigger of the GnRHa-induced cysts was one the managements while the efficiency is largely unknown. Objective: To investigate the effect of HCG trigger of GnRH agonist-induced functional ovarian cysts (FC) on clinical pregnancy rate in FET cycles pretreated with GnRHa. Methods: 657 cycles underwent HRT-FET with GnRHa pretreatment were retrospectively analyzed. Patients were divided into the functional cysts (FC) group and no functional cysts (NC) group according to whether the patient developed FC (follicular diameter≥7mm and E2≥100pg/ml). Risk factors associated with the incidence of GnRHa-induced FC were determined by multivariate regression analysis. Pregnancy outcomes were compared between the FC group and NC group. Propensity score matching (PSM) was performed to reduce the impact of confounding factors. Three multivariate regression models adjusted with confounding factors were performed to assess the association of HCG trigger of GnRHa-induced FC and clinical pregnancy. Interactive analysis and subgroup analysis based on age were analyzed by regression models. Results: The incidence of FC was 9.74% (64/675) in GnRHa pretreated frozen cycles. Older age (aOR 1.11, 95%CI 1.06~1.17, p-value<0.001) and lower BMI (aOR 0.85, 95%CI 0.74~0.97, p-value=0.02) are risk factors for incidence of GnRHa-induced FC. Implantation rate, clinical pregnancy rate (CPR), and miscarriage rate were not significantly different between the FC group and NC group before or after PSM (all p-values>0.05). Multivariate logistic models showed that HCG trigger of GnRHa-induced FC does not decrease CPR in the general population (all p-values>0.05). Interactive analysis showed that the effect of HCG trigger of GnRHa-induced functional ovarian cysts on clinical pregnancy is interactive with age (p-value for interaction: 0.002). HCG trigger is associated with significantly higher CPR compared to HRT-FET cycles without functional ovarian cysts in patients≥35 years (aOR 4.40, 95%CI 1.57~12.3, p-value=0.005). Conclusions: HCG trigger of GnRHa-induced FC does not decrease the chance of clinical pregnancy in HRT-FET cycles with GnRHa pretreatment.